Вы находитесь на странице: 1из 8

# Common Derivatives and Integrals

Basic Properties/Formulas/Rules
d
( cf ( x ) ) = cf ( x ) , c is any

Derivatives

( f ( x ) g ( x ) ) f ( x ) g ( x )
=

constant.
dx
d

( x ) = nx
n

n-1

d
( c ) = 0 , c is any constant.
dx

, n is any

number.
dx

( f g ) = f g + f
d

( f ( g ( x ))) (

( ))

x)

=
dx
d

g (Product Rule) f
f g - f g (Quotient Rule)
=
2
g
g
f g x g (Chain Rule)

g ( x)

(e )
( )

=g( x) e

g(x)
d
ln g ( x ) ) =
(
dx
g( x)

dx
Common Derivatives
Polynomials
d
d
c)=0
(
( x)=
dx
1
dx
Trig Functions
d
sin x ) = cos
x dx(
d
sec x ) = sec x tan
x dx(
Inverse Trig Functions
d
1
( sin -1 x ) = 2
dx
1- x
dx
d
1
-1
sec x ) =
(
2
dx
x x -1

d
cx =
c dx( )

( x ) = nx
n

n-

d
n
n -1
cx ) = ncx
(
dx

dx
d
cos x ) = - sin
x dx(
d
csc x ) = - csc x cot
x dx(

d
tan x ) = sec 2
x dx(
d
cot x ) = - csc2
x dx(

( cos

-1

x) =-

1- x
dx
1

d
-1
csc x ) = (
dx
x

x -1

( tan

-1

1
x) =
2
1+x

d
1
-1
cot x ) = - 2
(
dx
1+x

Exponential/Logarithm Functions
dx
d
x
x
a
=
a
ln
(
( )
a)
Visit http://tutorial.math.lamar.edu for a complete set of Calculus I & II notes.

2005

Paul Dawkins

dx

(ex ) = ex

1
,
dx

( ln ( x ) ) =

x>0

## Hyperbolic Trig Functions

d
sinh x ) = cosh
x dx(
d
sech x ) = - sech x tanh
x dx(

d
,
dx

( ln x ) =

1 x0

d
cosh x ) = sinh
x dx(
d
csch x ) = - csch x coth
x dx(

## Visit http://tutorial.math.lamar.edu for a complete set of Calculus I & II notes.

1 x>0
d
log a ( x ) ) =
(
dx
,
x ln a

d
tanh x ) = sech 2
x dx(
d
coth x ) = - csch 2
x dx(

2005

Paul Dawkins

Integrals

Basic Properties/Formulas/Rules

cf ( x ) dx = c f ( x ) dx , c is a

f ( x ) g ( x ) dx = f ( x ) dx g ( x )

constant.

dx

a f ( x ) dx = F ( x = F ( b ) - F (
a)

)a

where F ( x ) = f ( x ) dx

cf ( x ) dx =

c dx = c ( b - a

a f ( x ) dx =
-
b

f ( x ) g ( x ) dx
=

a
a f ( x ) dx =

f ( x ) dx , c is a constant.

f ( x ) dx = f ( x ) dx + f ( x )
dx

b
a

f ( x ) dx g ( x ) dx

f ( x ) dx

If f ( x ) on a x b then f ( x ) dx 0
a
0
b
b
If f ( x ) g ( x ) on a x then f ( x ) dx g ( x ) dx
a
b

Common Integrals
Polynomials

k dx = k x +

dx = x + c

1 dx = ln x +

c
x
1

-1

dx = ln x +

1 n+1
x dx =n + 1 x + c, n -1
n

-n

x dx =

c
p

dx = ln ax + b +

c
ax + b
a

x q dx =

1
- n +1
x
+ c, n 1
-n + 1

+
1

+c=

q
q

q
x
p+q

p+ q
q

+c

+1

Trig Functions

## sec u tan u du = sec u

cos u du = sin u + c

+c

tan u du = ln sec u + c
sec u du = ln sec u + tan u
+c

sin u du = - cos u + c
csc u cot udu = - csc u

sec u du = tan u + c
csc2 u du = - cot u + c

+c

## csc u du = ln csc u - cot u + c

2
1

cot u du = ln sin u + c
1
sec u du = sec u tan u + ln
sec u + tan u + c
Exponential/Logarithm Functions

eu du = eu +

e
au

au

u du =
csc
c 3
2
) 3
)

a du =

a
+c
ln a

+ c 2 ( a sin ( bu ) - b cos ( bu ) )
a +b
eau
au
e cos
bu
du
(
)
+ 2c 2 ( a cos ( bu ) + b sin ( bu ) )
=
a +b

= e

sin ( bu ) du

- csc
( u cot u + ln csc u - cot u +

ln u du = u ln ( u ) - u + c
u

ue du = ( u -1) e
1

u ln u

+c

## Inverse Trig Functions

1

-1 u
du = sin
+
c
a
2

a -u2
1
1
-1 u
du = tan +
c 2

a
2
a

a +u
1
1

-1 u
du = sec
+
c

a
a
2 u u 2
a

-1

sin u du = u sin
+

-1

u 1-u +c

tan

-1

u du = u tan

-1

u - ln (1 + u
2

) +c

-1
-1
2
- cos u du = u cos u 1 - u + c

## Hyperbolic Trig Functions

cosh u du = sinh u + c

sinh u du = cosh u + c

sech

u du = tanh u + c

## csch coth u du = - csch u + csch u du = - coth u + c

sech tanh u du = - sech u +
c
c
sech u du = tan -1 sinh u
tanh u du = ln ( cosh u ) + + c
c
Miscellaneous
1
u+a
1
du =
ln
+
c
2
2a u - a

a -u
2

a 2 + u 2 du =

u 2 - a 2 du =

a2 + u 2 +
+
2
u

u 2 - a2 +

2
2
2
u a - u du =

a -u +

u
2
- a

a
2
2a
2
a2

ln u a + u

du =
2

1
2a

ln

u- a

+c

u+a

+c

ln u u - a + c

sin

-1

+c

2
2
a
2
a
u2
-1 a - u
2
2au - u +
cos
+c
a 2au - u du =

2
2
a
Standard Integration Techniques
Note that all but the first one of these tend to be taught in a Calculus II class.
u Substitution
b

Given

## a f ( g ( x ) ) g ( x ) then the substitution u = g ( x ) will convert this into the

dx

g (b )

integral, a f ( g ( x ) ) g ( x ) dx = g ( a ) f ( u ) du .
Integration by Parts
The standard formulas for integration by parts are,

udv = uv -
vdu

a udv = uv a - a vdu

Choose u and dv and then compute du by differentiating u and compute v by using the
fact that v = dv .

Trig Substitutions
If the integral contains the following root use the given substitution and formula.
2
2
a
and
cos q = 1 - sin
2
2 2
x = sin
a -b x

b x - a

a +b x

q
b
a
x = secq
b
a
x = tan q
b

q and

tan q = sec q
2

-1 and

sec q = 1 +

tan q

Partial Fractions
P(x)

## where the degree (largest exponent) of P ( x is smaller than the

If integrating
Q(x)
dx

degree of Q ( x ) then factor the denominator as completely as possible and find the
partial fraction decomposition of the rational expression. Integrate the partial fraction
decomposition (P.F.D.). For each factor in the denominator we get term(s) in the
decomposition according to the following table.
Factor in Q ( x

Term in P.F.D

A
ax
b +

( ax + b )

A1

ax +
b

ax + b

ax + bx +
c

Ax + B
ax + bx +
c
2

( ax
)

+ bx + c

A2

( ax + b )

Ak

( ax + b )k

A1 x + B1
ax + bx +
c
2

+L+

Ak x + Bk
+ L +2
( ax + bx + c )k

## Products and (some) Quotients of Trig Functions

sin

tan

x cos x dx

1. If n is odd. Strip one sine out and convert the remaining sines to cosines using
2
2
sin x = 1 - cos x , then use the substitution u = cos x
2. If m is odd. Strip one cosine out and convert the remaining cosines to sines
2
2
using cos x = 1 - sin x , then use the substitution u = sin x
3. If n and m are both odd. Use either 1. or 2.
4. If n and m are both even. Use double angle formula for sine and/or half angle
formulas to reduce the integral into a form that can be integrated.
m

x sec x dx

1. If n is odd. Strip one tangent and one secant out and convert the remaining
tangents to secants using tan 2 x = sec 2 x -1 , then use the substitution u = sec x

2. If m is even. Strip two secants out and convert the remaining secants to tangents
2
2
using sec x = 1 + tan x , then use the substitution u = tan x
3. If n is odd and m is even. Use either 1. or 2.
4. If n is even and m is odd. Each integral will be dealt with differently.
Convert Example : cos x = ( cos x )3 = (1 - sin x )3
6